PS01.213: COMPARISON OF MANUAL VERSUS MECHANICAL INTRA-THORACIC ESOPHAGO-GASTRIC ANASTOMOSIS IN RADICAL 2-STAGE MINIMALLY INVASIVE ESOPHAGECTOMY FOR CANCER. (14th September 2018) - Charalabopoulos, Alexandros; Farhangmehr, Neda; Akitikori, Temisanren; Shanmuganathan, Kanatheepan; Soile, Oluwasunmisola; Hussain, Aadil; Tang, Cheuk; Venkatesh Jayanthi, Naga; Lorenzi, Bruno
Abstract: Background: While in open esophagectomy a plethora of studies comparing outcomes of mechanical (circular or linear stapler) versus hand-sewn intra-thoracic anastomosis have been published, little evidence exists regarding 2-stage minimally invasive esophagectomy; In the majority of published studies the mechanical anastomosis is favored. Construction of the intra-thoracic esophago-gastric anastomosis in minimally invasive esophagectomy is the procedure's rate limiting step. We aim to present our results of hand-sewn versus mechanical anastomosis in 2-stage minimally invasive esophagectomy. Methods: Data of 113 consecutive patients over a 20-month period that underwent 2-stage minimally invasive esophagectomy for cancer in our institution were analyzed. Inclusion criteria included only 2-stage and only minimally invasive esophagectomies for cancer. 43 cases underwent fully minimally invasive esophagectomy and 70 had laparoscopic-assisted hybrid esophagectomy. A fully hand-sewn anastomosis with 3/0 v-lock barbed suture was formed in 38% of cases and a mechanical anastomosis with a 25mm or 28mm circular stapler was formed in 62% of cases. Comparison between anastomotic techniques was assessed through Chi-Square and Log-Rank analysis. Results: Median age was 68(IQR, 47–82) in manual anastomosis group and 65(IQR, 31–81) in circular stapler group. Of the manual anastomosis group, 74% received neo-adjuvant treatment versus 20% of the mechanical anastomosis group. In the manual anastomosis group n = 3(6.97%) developed a leak; of these, n = 2 were stented and n = 1 was subclinical requiring no intervention. There was one sepsis-related death; 30-day mortality was 2.3%. In the mechanical anastomosis group n = 2(2, 8%) developed anastomotic leak (one combined with tracheo-esophageal fistula) and both were stented and eventually resulted in mortality. 30-day mortality was 2.8%. No conduit necrosis was noticed. Anastomotic strictures requiring dilatation were seen in n = 4(9.3%) in the manual anastomosis group versus n = 5(7.1%) in the mechanical anastomosis group. No statistically significant difference was found between the groups in terms of leak ( P  = 0.312), stricture ( P  = 0.698) and mortality rate ( P  > 0.005). Median length of stay was 11 days (7–70) in the manual anastomosis group and 12 days (7–51) in mechanical anastomosis group. Conclusion: Outcomes between manual and mechanical intra-thoracic anastomosis in minimally invasive esophagectomy show no difference within our study group. Both are equally safe and efficient, with surgeon's preference taking priority. Disclosure: All authors have declared no conflicts of interest.